2010
DOI: 10.1007/s00228-010-0805-6
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian medical students’ attitudes towards the pharmaceutical industry

Abstract: Norwegian medical students are opinionated, critical and curious with respect to pharmaceutical industry relations. This interest can be explored and probably also modified by educational initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 17 publications
5
39
0
3
Order By: Relevance
“…A study conducted among Norwegian fifth-year and sixth-year medical students in Norway and in Hungary/Poland in 2008-09 showed that 74 % of them had had varying degrees of contact (meeting or conversation with a representative) with the pharmaceutical industry (13). The students in Poland and Hungary had actually had the least contact with the pharmaceutical industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted among Norwegian fifth-year and sixth-year medical students in Norway and in Hungary/Poland in 2008-09 showed that 74 % of them had had varying degrees of contact (meeting or conversation with a representative) with the pharmaceutical industry (13). The students in Poland and Hungary had actually had the least contact with the pharmaceutical industry.…”
Section: Discussionmentioning
confidence: 99%
“…Six out of ten Norwegian medical students reported having a positive or neutral relationship with the pharmaceutical industry (13). The remainder stated that they were critical to having connections with the industry, and the authors have discussed whether this could be related to the national decision in 2005 for 'the teaching in the medical degree programme to be organised without the financial or practical involvement of private companies or industry' (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency of exposure to pharmaceutical promotion increases with each additional academic year [2], [4], [5]. In the final clinical year up to 90 percent of medical students reported indirect or direct contact to pharmaceutical promotion or sales representatives as well as participating in sponsored events [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the final clinical year up to 90 percent of medical students reported indirect or direct contact to pharmaceutical promotion or sales representatives as well as participating in sponsored events [2], [3]. Accepting small gifts, free meals and educational material sponsored by the pharmaceutical industry is considered to be normal, appropriate and ethically unobjectionable by most students [2], [3], [4], [6]. Frequent exposure of medical students to pharmaceutical promotion was associated with a general positive attitude toward the pharmaceutical industry [4], [7] and confidence in dealing with pharmaceutical marketing strategies [4].…”
Section: Introductionmentioning
confidence: 99%